Neuroprotective Efficacy of Quercetin with Lamotrigine and Gabapentin Against Pentylenetetrazole-induced Kindling and Associated Behavioral Comorbidities in Mice - Shrivastava, Aman; Gupta, Jeetendra Kumar; Goyal, Manoj Kumar (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: Epileptic seizure is a widespread neurological condition with multifaceted physiology. Numerous scientific data advise a therapeutic efficacy of bioflavonoids or bioactive compounds in epilepsy against oxidative stress pathway. Thus, the main objective of this investigation has been undertaken to explore the potential neuroprotective efficacy of Quercetin (Que) bioflavonoid with selected anti-epileptic drugs (AEDs) against pentylenetetrazole (PTZ) induced kindled model of convulsions in mice. Materials and Methods: Swiss albino mice (20-30 g) were individually separated into seven groups (n = 6). Before PTZ administration, quercetin was dissolved in 0.6% w/v carboxymethylcellulose (CMC) sodium and served for 7 days orally. On the seventh day, 30 minutes before PTZ administration, Lamotrigine (Lmt) and Gabapentin (Gbp) were solubilized with saline and given as single intraperitoneal (i.p.) injections. PTZ (30 mg/kg, i.p.) was given in a sub convulsive dose on alternate days for 12 days until the mice seemed to have complete motor seizures. Results: PTZ dosage in the sub-convulsive range (30 mg/kg, i.p., every other day for 12 days) resulting in a progressively rise in convulsive behavior (seizure score). Que (20 mg/kg) + Lmt (15 mg/kg, i.p.) administration for 12 days exhibited improvement in transfer latencies. In a histopathological study, microphotographs (×40) of brain tissue of mice showed cell morphology in the different experimental treated groups. Conclusion: Quercetin has been reported to provide antioxidant efficacy as a potent bioactive compound when treated with the combination of quercetin and lamotrigine, which exhibited significant modulation in their neuroprotective efficacy.
Keywords: Lamotrigine; Neuroprotective effect; Anticonvulsant activity; Kindling model; Quercetin; Histopathological study